Automotive Disruption and the Urban Mobility Revolution Rethinking the Business Model 2030 - Lempp, Martin; Siegfried, Patrick (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides an integrated perspective of the automotive market for the next decade. It shows how customers and producers are shaping the market simultaneously and contends that the first steps of the mobility revolution have already been taken. It compels automotive companies to strike new paths to participate in this journey. The authors provide a comprehensive analysis of the automotive industry, including prevailing business models of OEMs and 'tier-n' automotive suppliers, the competitive environment they are embedded in as well as socio-economic changes affecting future market conditions. Subsequently, elements of the automotive disruption are presented; these enable the provision of novel urban mobility concepts and offer a new source for additional services accompanying the user. A comprehensive insight into consumer behavior, potential automotive business models which can be sustained by 2030, smart city models, transformation strategies, and diverse market penetration scenarios are also provided in the book. It also outlines the challenges and key actions that shape the automotive sector even beyond 2030 as well as knock-on effects across different industries arising from the technological and economic changes in the automotive market are projected.
1. Introduction to Automotive Disruption and the Urban Mobility Revolution -- 2. Characterization of the Automotive Industry -- 3. Elements of the Automotive Disruption -- 4. Urban Mobility Revolution: A Quantitative Analysis -- 5. Business Model 2030: A Metamorphosis of the Automotive Landscape -- 6. Conclusion to Automotive Disruption and the Urban Mobility Revolution -- 7. Prospects: A Look Beyond.
Keywords: Automobile industry and trade; Strategic planning; Leadership; Sustainability; Technological innovations; Automotive Industry; Business Strategy and Leadership; Sustainability; Innovation and Technology Management